Internet based econometric computing - Wolfgang Karl Härdle; Joel L. Horowitz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
Modern econometrics requires implementation of highly specialized software. In contrast to mathematical arguments used in implementing new econometric techniques the corresponding software algorithms require specific platforms. The specialization of hardware and software, in fact, seriously impedes the adoption of new methods in applied research. It complicates the proliferation of new techniques and makes it difficult to motivate students to use the methods and to help students to develop an intuitive understanding of the methods in applications. We discuss the potential for reducing these problems through Internet-based econometric computing and instruction. We refer to existing examples of net-based teaching and present concrete examples for interactive teaching of elementary econometrics and statistics.
urn:nbn:de:kobv:11-10056812
Keywords: 330